'Fides mater virtutum est': Peter Martyr Vermigli's disagreement with Thomas Aquinas on the 'form' of the virtues. Issue 1 (5th February 2014) - Parker, Eric M.
Abstract : Peter Martyr Vermigli's elevation of faith over charity displays similarities and differences with Thomas Aquinas and other medieval authors. For Thomas, faith does not perceive its object and thus denotes an uncertain assent to imperfectly revealed truths. Aquinas posits a reordering of will and intellect in order to explain how faith is more certain than ' scientia. ' Vermigli on the other hand attempts to maintain the natural order between intellect and will in virtuous action (that is, natural law) even for the theological virtues. He likens faith to vision and practical wisdom arguing that God illuminates the mind to make the object of faith apprehensible to the judgment of reason. This perspective presents a more optimistic account of temporal, intellectual perfection via grace.